POTENTIAL ROLE OF WILD CRUCIFERS IN THE PRESERVATION OF DIADEGMA EUCEROPHAGA HORSTMAN (HYMENOPTERA: ICHNEUMONIDAE), A PARASITOID OF THE DIAMONDBACK MOTH, PLUTELLA XYLOSTELLA LINNAEUS (LEPIDOPTERA: PLUTELLIDAE) - UTOMO KARTOSUWONDO (Biotropia: The Southeast Asian Journal of Tropical Biology, 2011)
Laboratory and  field experiments were conducted to evaluate the potential role of  two species of wild crucifers  in the preservation of Diadegma eucerophaga Horstman, a parasitoid of  the diamondback moth, Plutella xylostella Linnaeus. In the laboratory, D. eucerophaga developed quite well on P. xylostella larvae fed on leaves of two species of wild cruciferous plants, Nasturtium heterophyllum BL. and Cardamine hirsuta L. These wild crucifers may serve as food and oviposition sites for P. xylostella. In the field, N. heterophyllum and C.  hirsuta  planted  adjacent  to  insecticide-treated  cabbage  plots  provided  refuge  for  D.  eucerophaga parasitoids.